ORGANIZATION OF PROJECT ACTIVITIES IN TRAINING IN EDUCATIONAL ROBOTICS OF FUTURE TEACHERS OF INFORMATICS - Shekerbekova Ш.Т.; Abdulkarimova Г.А.; Arynova Г.С.; Erbol А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article analyzes the experience of organizing project activities in teaching educational robotics to bachelors, future teachers of informatics. The main methodological possibilities of using this method for the formation of basic competencies are considered: the foundations of design, programming, the ability to work with the online constructor TRIK Studio, as well as the development of skills for collective research activities. The article formulates the stages of work on the project and the functions of its participants within the discipline «Educational robotics». The analysis of projects completed by students in the online constructor TRIK Studio was also carried out: the movement of the robot in a circle, along a line and along a maze. Based on the experience of using project activities, certain aspects of the implementation of project activities in teaching students have been established. Project activity allows you to implement your ideas and analyze the results of research, i.e., acquire new knowledge and skills that cannot be acquired using theoretical teaching methods.